Dual Pro- and Anti-Inflammatory Features of Monocyte-Derived Dendritic Cells - Azeem, Waqas; Bakke, Ragnhild Maukon; Appel, Silke; Øyan, Anne Margrete; Kalland, Karl-Henning (Frontiers in Immunology, 2020)
The transcription factor β-catenin is able to induce tolerogenic/anti-inflammatory features in different types of dendritic cells (DCs). Monocyte-derived dendritic cells (moDCs) have been widely used in dendritic cell-based cancer therapy, but so far with limited clinical efficacy. We wanted to investigate the hypothesis that aberrant differentiation or induction of dual pro- and anti-inflammatory features may be -catenin dependent in moDCs. β-catenin was detectable in both immature and lipopolysaccharide (LPS)-stimulated DCs. The β-catenin inhibitor ICG-001 dose-dependently increased the pro-inflammatory signature cytokine IL-12p70 and decreased the anti-inflammatory signature molecule IL-10. The β-catenin activator 6-BIO dose-dependently increased total and nuclear β-catenin, and this was associated with decreased IL-12p70, increased IL-10 and reduced surface expression of activation markers, such as CD80 and CD86, and increased expression of inhibitory markers, such as PD-L1. 6-BIO and ICG-001 competed dose-dependently regarding these features. Genome-wide mRNA expression analyses further underscored the dual development of pro- and anti-inflammatory features of LPS-matured moDCs and suggest a role for β-catenin inhibition in production of more potent therapeutic moDCs.